GREEN WORD OF MOUTH, GREEN KNOWLEDGE, GREEN VALUE, DAN PURCHASE INTENTION PRODUK TUMBLER PADA GENERASI Z - Rosyihuddin, Muhammad; Krisnawati, Wenti (Jurnal Riset Entrepreneurship, 2025)
Environmental degradation due to the use of single-use plastics has prompted the younger generation to reconsider their consumption patterns. This study aims to examine the influence of Green Word of Mouth (GWOM), Green Knowledge (GK), and Green Value (GV) on Purchase Intention (PI) or the intention to buy environmentally friendly tumbler products among Generation Z in Gresik, Indonesia. As a digital generation, Gen Z is at the intersection of global ecological awareness and daily consumption decisions. This study uses a quantitative approach involving 100 respondents selected through a purposive sampling technique. Data analysis was conducted using SmartPLS 4 to test the direction of influence and research hypotheses, in order to determine the relationship between variables. The results show that the three variables: GWOM, GK, and GV have a positive and significant effect on purchase intention, with Green Value being the strongest predictor. This finding confirms that internalized environmental values are the main driver of sustainable consumption behavior, which is then strengthened by peer communication and ecological literacy. This study provides a strong theoretical contribution to the model of green consumer behavior, while also providing practical implications for marketers and policymakers in encouraging more environmentally conscious consumption. Through communication strategies that align with the values of the younger generation and authentic green narratives, behavioral change towards a sustainable future can be accelerated.